The Development of an Interactive Canva-Based PowerPoint on the Theme Familie to Enhance Reading Skills of Grade XI Students at SMAN 1 Gedangan - Irania, Fanny Pudji; Titaley, Audrey (LATERNE, 2025)
An interactive PowerPoint based on Canva combined text, images, audio, and hyperlinks to make learning more interesting. The development of this interactive PowerPoint was based on the problems that students had when learning German, especially in understanding simple reading texts on the topic of family. The aim of this research was to develop an interactive PowerPoint theme Familie based on Canva for the reading competence of class XI SMAN 1 Gedangan. The research method is based on the R&D (Research and Development) model of Borg and Gall, limited to the step of design revision. The validation by experts resulted in a rating of 96% for media and 92% for material. This showed that the Canva-based interactive PowerPoint learning media on Familie theme for reading skills was suitable for Grade XI students of SMAN 1 Gedangan. Based on the results of the research, it can be concluded that the interactive PowerPoint based on Canva, which was developed by combining text, images, audio, and hyperlinks and referred to the Borg and Gall development model, proved to be feasible for use in improving the German reading skills of 11th grade students at SMAN 1 Gedangan, with validation results showed a feasibility level of 96% for the media and 92% for the material. Keywords: Interactive PowerPoint, German reading skills, Canva